Therapeutic potential of multi-targeting phytochemicals derived from Apium graveolens ethanol extract in West Java, Indonesia against multidrug-resistant Pseudomonas aeruginosa (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Sufa HI, Kurniati I, Dermawan A, Abror YK, Indra AIN, Purkon DB. 2024. Therapeutic potential of multi-targeting phytochemicals derived from Apium graveolens ethanol extract in West Java, Indonesia against multidrug-resistant Pseudomonas aeruginosa. Biodiversitas 25: 2183-2190. This study aims to evaluate the antibacterial efficacy of Apium graveolens (AG) extract from West Java, Indonesia against MDR-P. aeruginosa species responsible for nosocomial infection. Several assessments of antibacterial activity in vitro were conducted, including the enumeration of bacterial colonies, the measurement of the inhibition zone by agar well diffusion, determination of Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) values, and the observation of cell damage using Scanning Electron Microscopy (SEM). The results have demonstrated that AG extract from West Java, Indonesia, possesses significant potential as an antimicrobial agent against MDR-P. aeruginosa. The Apium graveolens extract, at concentrations of 50, 100, and 200 mg/mL, reduced MDR-P. aeruginosa colonies by 59.3%, 65.7%, and 82%, respectively. The inhibition zone sizes ranged from 7 to 12 mm for 50 mg/mL, 8 to 16 mm for 100 mg/mL, and 16 to 17 mm for 200 mg/mL. The MIC values of 100 mg/mL for PA1 and PA3, 200 mg/mL for PA2, with an MBC value of 200 mg/mL for each test. Scanning electron microscope observation indicated that treatment with 100 mg/mL of AG extract caused significant damage to bacterial cells. In conclusion, A. graveolens extracts show promise as potential antibacterial agents against nosocomial infections caused by MDR-P. aeruginosa. Further research, including in vivo studies of the antibacterial mechanism of action, is warranted.